Social Media Health Communication, Psychological Distress, and the Conditional Roles of Information-Seeking Self-Efficacy, Wearable Adoption, and Age - Dehou You; Chengyu Xu; Hongyan Lai; Mengxin Ding; Xiaoran Zhang; Dianshi Moses Li (Eureka, 2026)
Social media increasingly carries health information, yet frequent engagement may coincide with psychological strain and may not affect all users in the same way. Using 4,991 complete cases from the U.S. Health Information National Trends Survey 6, this cross-sectional study examined whether information-seeking self-efficacy statistically linked social media health communication to psychological distress and whether wearable-device adoption and age conditioned that association. Unweighted ordinary least squares models and 5,000-draw percentile bootstrap intervals were estimated, with effects also expressed as conceptual-range percentage coefficients. Social media health communication was positively associated with distress (bₚ = .236, p < .001). It was also positively associated with information-seeking self-efficacy, but self-efficacy was not independently associated with distress; consequently, the indirect effect was not distinguishable from zero (bₚ = −.0045, 95% bootstrap CI [−.0125, .0031]). Wearable adoption dampened the communication–self-efficacy association, and this difference became more negative with age (three-way bₚ = −.758, p < .001). However, the index of moderated moderated mediation also included zero. The results identify conditional variation in search confidence, not a supported mediated pathway to distress, and should be interpreted as unweighted cross-sectional associations rather than causal or population estimates.